LANDSLIDE RISK ASSESSMENT IN O.V. FOMIN BOTANICAL GARDEN - Kostyuchenko, M.; Mokienko, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Landslides on the right-bank of Kyiv has always caused serious problems. There are some natural and artificial conditions and causes which facilitate the development of the landslides on this territory. Due to the increased anthropogenic influence and climatic changes this problem has become urgent at the present time. In April 2013 the sharp warming and intensive melting of snow in the Kyiv resulted was in the formation of more than a hundred new landslide areas, including those formed within the territory of the botanical garden named after O. Fomin. In order to assess possible danger of further landslide development a detailed observationas well as handy well drilling have been carried out during May 2014 such within the central section of the landslide body. Researches are mabe by scintific workers of Taras Shevshenko National University of Kiev. The results obtained results have shown that the a structural consequent landslide with distinctly manifested sliding surface is developed within landslide. A. Numerous cracks are found in the middle part of the landslide body and the shaft bulging is formed. The coefficients of slope stability under various conditions are obtained. The results of current research and further observations have revealed that the landslide process reamian active.
Keywords: landslide; technogenic impact; climate change; monitoring of geological environment